Perancangan dan Pengembangan E-Learning pada Mata Kuliah Metode Penelitian di Fakultas Keguruan dan Ilmu Pendidikan Universitas Mahaputra Muhammad Yamin - Afrahamiryano, Afrahamiryano; Ariani, Dewi (Jurusan PIPS FKIP UMMY Solok, 2017)
E-learning is designed to develop the skills of audio, visual and kinetic student. The development of e-learning is done through a research and development (Research and Development) using a modified model of the development of the development model Borg & Gall. The procedure of the study include: needs analysis, setting goals, product development, revision, validation, product testing, revision and final products. Products made using Camtasia software 7. The research has reached the stage develop. The purpose is to make the development of e-learning products that can optimize the ability of audio, visual and kinetic student. Furthermore, e-learning products tested and validated by a validator (expert). Based on the results of the validation and testing of products in the lecture note that the e-learning products is valid and effective for Educational Research Methods lecture.